AgriTech4Kenya Innovation Challenge: Bootcamp Pitch Event, 29 November 2024 - Khader, Taija; Bhansali, Malvika; Wafullah, Nekesah (2024)
From November 25th to 29th, 2024, 25 selected teams converged in Limuru, Kenya, for a dynamic and interactive Bootcamp experience. This intensive four-day event provided participants with tailored technical mentorship, business strategy sessions, a field visit, and invaluable networking opportunities. The highlight of the Bootcamp was the Pitch Event on November 29th, held during Kenya Innovation Week. At this occasion, innovators showcased their groundbreaking solutions to a distinguished panel of industry leaders, investors, and strategic partners.